The Impact of Gross Motor Function on the Oral Health-Related Quality of Life in Young Adults with Cerebral Palsy in Saudi Arabia - Sharat Chandra Pani; Saja Fahad AlEidan; Rawan Nasser AlMutairi; AlJawharah Ali AlAbsi; Dalal Nasser AlMuhaidib; Hessa Faisal AlSulaiman; Najd Waleed AlFraih (International Journal of Dentistry)
Background. There is evidence that gross motor function impacts the health-related quality of life of young adults with cerebral palsy. This study aimed to assess gross motor function, oral health and oral health-related quality of life (OHRQoL), and the relationship between them in young adults with cerebral palsy. Methods. The sample comprised 46 individuals aged between 13 and 17 years with Gross Motor Function Classification Scores (GMFCS) ranging from level I to level III. The individuals and their parents were administered an Arabic version of the child perception questionnaire for adolescents. Parental and child perception scores, DMFT, and gingival index were compared across GMFCS levels using the one-way ANOVA and Scheffe’s post hoc test. Results. Children with level III GMFCS had a significantly higher child perception score (CPQ) and parental perception score (PPQ) than those with level I or level II scores. There was a significant association between function (GMFCS) and the CPQ score in children (p=0.016). No significant associations were found between the CPQ score and either dental caries (DMFT) or gingival bleeding (GI) scores. Children with GMFCS level III had a significantly higher DMFT (p=0.002) and GI (p=0.001) scores. Conclusion. Motor function has a significant impact on both the oral health and the OHRQoL of adolescents and young adults with spastic cerebral palsy.